The degree to which mhich mathematic teachers practice social networking skills - Ghufran abd Hassan / Luma Ahmed Ali / Alaa Muhammed Kazem ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The aims of the current research is to identify the degree to which mathematics teachers practice social networking skills, as the researchers adopted the descriptive approach to their research, and to verify this, a questionnaire was prepared and applied to a sample of (300) mathematics teachers in Baghdad Governorate / Al-Rusafa Secondary Education during the second semester of the year 2021 / 2022 AD, where only (170) of them were adopted, whereas the rest were neglected because they are not suitable for statistical analysis. The results showed that the teachers practice of the social networking skills were low for some aspects, furthermore the absence of a statistically significant difference between the average responses of teachers on the questionnaire. In light of these results, the researchers presented recommendations and suggestions, conducting more studies on the use of social media among teachers, Engaging the role of social networks in schools to increase the awareness of teachers and learners of its importance, and providing an Internet network in schools.